Ski jumping boots limit effective take-off in ski jumping - Virmavirta, M.; Komi, P. V. (Journal of Sports Sciences, 2001)
In this study, we measured the vertical and horizontal take-off forces, plantar pressures and activation patterns of four muscles (vastus lateralis, gluteus maximus, tibialis anterior, gastrocnemius) in 10 ski jumpers in simulated laboratory conditions when wearing either training shoes or ski jumping boots. We found significant differences in vertical (P < 0.001), horizontal (P < 0.05) and resultant (P < 0.001) take-off velocities and vertical force impulse (P < 0.01). We found no significant differences in the jumpers' initial take-off positions; however, the jumping boots condition resulted in a smaller displacement in the final position of the following joint angles: ankle angle (P < 0.001), knee angle (P < 0.001), hip angle (P < 0.01) and shank angle relative to the horizontal (P < 0.01). This corresponds with less electromyographic activity during take-off in both the gastrocnemius (300 to 200 ms and 200 to 100 ms before take-off) and gluteus maximus (300 to 200 ms and 100 to 0 ms before take-off). During the early take-off in the jumping boots condition, significantly more pressure was recorded under the heel (P < 0.001), whereas the forefoot was more highly loaded at the end of the take-off. Differences in take-off velocity (representing the final output of the take-off) can be accounted for in the main by the different use of plantar flexion, emphasizing the role of the knee and hip extensors when wearing jumping boots. We conclude that the stiffness of the structure of the jumping boots may result in a forward shift of pressure, thus limiting the effective vertical force. To avoid this pressure shift, the pattern of movement of simulated take-offs should be carefully controlled, particularly when wearing training shoes.